Кон Quentin Meillassoux, Après la finitude. Essai sur la nécessité de la contingence: Për Quentin Meillassoux, Après la finitude. Essai sur la nécessité de la contingence - Sekulovski, Jordančo; Ahmeti, Lindita (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Jordančo Sekulovski | Јорданчо Секуловски Title (Macedonian): Кон Quentin Meillassoux, Après la finitude. Essai sur la nécessité de la contingence Title (Albanian): Për Quentin Meillassoux, Après la finitude. Essai sur la nécessité de la contingence Translated by (Macedonian to Albanian): Lindita Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No. 2 (Summer 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 185-186 Page Count: 2 Citation (Macedonian): Јорданчо Секуловски, „Кон Quentin Meillassoux, Après la finitude. Essai sur la nécessité de la contingence“, Идентитети: списание за политика, род и култура, т. 5, бр. 2 (лето 2006): 185-186. Citation (Albanian): Jordančo Sekulovski, „Për Quentin Meillassoux, Après la finitude. Essai sur la nécessité de la contingence“, përkthim nga Maqedonishtja Lindita Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 5, No. 2 (Summer 2006): 185-186.